Detection of infectious enteroviruses by an integrated cell culture-PCR procedure. - Reynolds, K A (1996)
Rapid detection of infectious enteroviruses in environmental samples was made possible by utilizing an integrated cell culture-reverse transcriptase PCR approach. By this method, the presence of infectious enterovirus was confirmed within 24 h, compared with > or = 3 days by cell culture alone. The combined methodology eliminated typical problems normally associated with direct reverse transcriptase PCR by increasing the equivalent volume of environmental sample examined and reducing the effects of inhibitory compounds.